Blood activity of glutathione peroxidase and its correlation with blood selenium concentration in grazing dairy cattle - Ceballos, Alejandro; Wittwer, Fernando German; Contreras, Pedro Alberto; Quiroz, Eduardo; Bohmwald, Helga Lidia (Pesquisa Agropecuaria Brasileira, 1999)
Selenium (Se) is part of the antioxidant enzyme glutathione peroxidase (GSH-Px; EC 1.11.1.9) structure, whose blood activity is related to the blood level of selenium. This study was designed to validate the analytical method to analyze the GSH-Px blood activity at the Clinical Pathology Laboratory of the Universidad Austral de Chile, and to correlate it with blood Se level in dairy cattle from the South of Chile. Blood heparinized samples were taken from 112 dairy cows from eight dairy herds located at Valdivia province, Chile. A kinetic NADPH-dependent technique was used to analyze the blood GSH-Px, and the content of Se in blood and plasma was analyzed by neutron activation. The Se concentration in blood was analyzed in 12 samples to correlate GSH-Px blood activity with blood and plasma Se level. The inaccuracy and imprecision were 5.9% and 10%, respectively. The mean and standard deviation of the obtained values were 89 ± 45 U/g of hemoglobin (Hb). The correlation between blood selenium and blood GSH-Px activity was r=0.97 (P < 0.05). Accordingly, it is possible to analyze the blood activity of GSH-Px by using the described technique. The blood activity of GSH-Px was related to the blood selenium level.